INFLUENCE OF COOPERATIVE LEARNING MODEL OF STAD TYPE (STUDENT TEAM ACHIEVEMENT DIVISION) ON STUDENT LEARNING IN COOLING SYSTEMS IN CLASS XI TKRO1 STATE VOCATIONAL SCHOOL 1 PALANGKA RAYA ACADEMIC YEAR 2018/2019 - Bristasik Jalhe Beka Dede (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2019)
This study aims to determine the effect of Cooperative Learning Type Student Teams Achievement (STAD) Model on student learning outcomes in the Cooling System material at Kelas XI TKRO1 at SMK Negeri 1 Palangka Raya Academic Year 2018/2019. This study uses the Research Method True Experimental Design type Post-test Only Control Design. The population of this study was all class XI TKRO 1 and TKRO2 SMK Negeri 1 Palangka Raya academic year 2018/2019. The sample of this study was class XI TKRO1 with a total of 32 students in the experimental class and class XI TKRO2 with a total of 27 control class students. Both samples were given different treatments, experimental classes with the treatment of cooperative learning models of Student Teams Achievement Division (STAD) and control classes with lecture learning treatments. This research will assess 3 domains. The division of the domain is cognitive learning outcomes of 50%, affective 20%, and psychomotor 30%. The instrument for the cognitive domain is the test of student learning outcomes, and for the affective and psychomotor domains use the observation sheet. The results of data analysis calculation of the value of student learning outcomes after carrying out experimental research obtained a value of tcount = 3.6 from the results of the calculation compared with the value of table = 3.6> 2,003, then the answer to the research hypothesis is H1 accepted, while the average score data the students' score is 85 from the results, it is known that the value of all students exceeds the Minimum Completion Criteria (KKM), so it can be concluded that there is the effect of using the STAD type cooperative learning model on student learning outcomes in learning using STAD type cooperative learning system material cooler in class XI TKRO1 SMK Negeri 1 Palangka Raya academic year 2018/2019.